1989
DOI: 10.3758/bf03208154
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic, diotic, and monaural summation of loudness: A comprehensive analysis of composition and psychophysical functions

Abstract: In a series of six experiments, the method of magnitude estimation, constrained by a multivariate model, was used to assess the rules that govern the summation of the loudness of two-tone complexes. This methodology enabled us to specify the amounts of summation and simultaneously to construct the corresponding loudness scales.\The components had different frequency separations and in the different experiments were presented (1) dichotically, a different frequency to each ear; (2) diotically, to both ears; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Some early data suggested that the LDEL was approximately 10 dB (Hellman & Zwislocki, 1963); the monaural sound had to be 10-dB higher in level than the diotic sound for the loudness to be matched. Because a 10-dB change in level corresponds approximately to a twofold change in loudness, an LDEL of 10 dB is consistent with the idea that loudness (in sones) simply sums across ears (Algom, Ben-Aharon, & Cohen-Raz, 1989; Fletcher & Munson, 1933, 1937; Hellman & Zwislocki, 1963; Levelt, Riemersma, & Bunt, 1972; Marks, 1978). The 1997 model and the 2006 model were both based on the assumption that this was the case.…”
Section: Improving Predictions Of Binaural Loudness Summation—the 200supporting
confidence: 77%
See 1 more Smart Citation
“…Some early data suggested that the LDEL was approximately 10 dB (Hellman & Zwislocki, 1963); the monaural sound had to be 10-dB higher in level than the diotic sound for the loudness to be matched. Because a 10-dB change in level corresponds approximately to a twofold change in loudness, an LDEL of 10 dB is consistent with the idea that loudness (in sones) simply sums across ears (Algom, Ben-Aharon, & Cohen-Raz, 1989; Fletcher & Munson, 1933, 1937; Hellman & Zwislocki, 1963; Levelt, Riemersma, & Bunt, 1972; Marks, 1978). The 1997 model and the 2006 model were both based on the assumption that this was the case.…”
Section: Improving Predictions Of Binaural Loudness Summation—the 200supporting
confidence: 77%
“…The 2007 model accurately predicts a wide variety of data on the binaural perception of loudness, including the data of Scharf (1969), Keen (1972), Algom, Ben-Aharon, et al. (1989), Zwicker and Zwicker (1991), Sivonen and Ellermeier (2006), and Glasberg and Moore (2010).…”
Section: Improving Predictions Of Binaural Loudness Summation—the 200mentioning
confidence: 96%
“…Some early data suggested that the LDEL was $10 dB (Hellman and Zwislocki, 1963). Since a 10-dB change in level corresponds approximately to a twofold change in loudness (Stevens, 1957;Hellman, 1976), an LDEL of 10 dB is consistent with the idea that the loudness evoked by presenting a sound to both ears is the sum of the loudness (in sones) evoked by the sound at each ear separately Munson, 1933, 1937;Hellman and Zwislocki, 1963;Levelt et al, 1972;Marks, 1978;Algom et al, 1989).…”
Section: Introductionmentioning
confidence: 52%
“…Some authors have shown that the amount of binaural summation of loudness depends on the mode of presentation (diotic or dichotic), interaural level differences, spectral and temporal distribution, etc. (Algom et al, 1989;Zwicker and Zwicker, 1991). These data show that the mechanism of the binaural loudness summation is still uncertain and its explanation needs further study.…”
Section: Introductionmentioning
confidence: 77%